Comparison of the effect of kalsitrapine and metformin as adjunctive therapy in the treatment of infertility in women with polycystic ovary syndrome - Jalilvand, Faranak; Farzipour, Shahla; Amani, Firouz; Houshmandi, Susan; Naeimi, Sajjad (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Chronic anovulation is one of the most common causes of infertility. In women with polycystic ovary syndrome (PCOS), other factors related to oocyte quality or endometrial and nesting disorders may also play a role. Infertile and non-ovulatory women who tend to become pregnant are candidates for ovulation induction. The aim of this study was to evaluate the effect of Kalsitrapine and metformin on the treatment of patients with PCOS. Methods: The clinical trial study was performed on 80 female patients with PCOS who had referred to Ardabil city hospital for infertility treatment were randomly divided in two groups with personal consent. One group received Kalsitrapine and another group received metformin. Results: The mean age of all patients was 26.08±5.21. There was no significant difference between 2 groups in term of age and BMI. There was no statistically significant difference between the two groups in terms of primary and secondary infertility. The mean duration of infertility was 3.68±3.49 years. There was no statistically significant difference between the 2 groups in terms of infertility duration. There was no statistically significant difference between the 2 groups in terms of the type of menstrual cycle. The response rate to treatment was 17.5% in the metformin group and 10% in the Kalsitrapine group. There was no statistically significant difference between the 2 groups in terms of response to treatment. In comparison, none of the studied factors in the 2 groups was significantly associated with the response to treatment. Conclusions: It is true that the recovery rate of the herbal medicine Kalcitropine in this study was slightly lower than metformin, but due to the side effects of metformin, including lethargy, abdominal pain, diarrhea, headache, constipation, bloating, weight loss, heartburn, nausea and Vomiting, unpleasant taste of metal in the mouth In some people, such people may be prescribed kalcitrapine for a longer period of time to evaluate its effect.